2017
DOI: 10.1136/bmjopen-2016-015755
|View full text |Cite
|
Sign up to set email alerts
|

Association of workplace and population characteristics with prevalence of hypertension among Brazilian industry workers: a multilevel analysis

Abstract: BackgroundExposure to risk factors for hypertension may be influenced by the characteristics of the workplace, where workers spend most of their daily time.ObjectivesTo evaluate the association between features of the companies, particularly the presence of facilities to provide meals, and of population characteristics and the prevalence of hypertension, taking into account individual risk factors for hypertension.Material and methodsThis multilevel analysis was based on a cross-sectional study with individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
12

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 41 publications
2
4
0
12
Order By: Relevance
“…The increased likelihood of having hypertension by age, race, and obesity status is consistent with previous research [ 12 ]. In addition, in the Jackson Heart Study cohort, mean systolic blood pressure and diastolic blood pressure levels increased with age [ 13 ], and obesity is associated increased incidence of hypertension [ 14 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The increased likelihood of having hypertension by age, race, and obesity status is consistent with previous research [ 12 ]. In addition, in the Jackson Heart Study cohort, mean systolic blood pressure and diastolic blood pressure levels increased with age [ 13 ], and obesity is associated increased incidence of hypertension [ 14 ].…”
Section: Discussionsupporting
confidence: 91%
“…Age, race, and obesity status were associated with a higher prevalence of hypertension, as were specific occupational categories, such as installation, repair, maintenance, and production occupation groups. e increased likelihood of having hypertension by age, race, and obesity status is consistent with previous research [12]. In addition, in the Jackson Heart Study cohort, mean systolic blood pressure and diastolic blood pressure levels increased with age [13], and obesity is associated increased incidence of hypertension [14].…”
Section: Discussionsupporting
confidence: 87%
“…L'HTA dans notre étude est associée significativement à plusieurs facteurs à risque dont le sexe masculin, l'âge avancé (> 45 ans), le surpoids & l'obésité, le stress, le sédentarisme, le statut employé, l'antécédent familial fratrie ainsi que les connaissances de mesures de prévention. Plusieurs études de la littérature associent l'âge, l'obésité et l'HTA en milieu professionnel [13,14,16,17,22,37]. Le sexe est associé à l'HTA dans notre étude comme cela est évoqué dans plusieurs études [11,13,16,22,37,38].…”
Section: De L'analyse Multivariéeunclassified
“…In a Korean cohort females had a higher risk but the sex differential was not significant (J. H. Lee et al, 2011). Men had a significantly higher risk of hypertension than women in cross-sectional studies in the US (Owolabi et al, 2017), China (Gao et al, 2013;Huang et al, 2017;Liu et al, 2014;Yang et al, 2015), Brazil (Vinholes et al, 2017) and Malaysia (Abdul-Razak et al, 2016). In contrast, other cross-sectional studies have reported no sex difference in the US (Ong et al, 2007), Malaysia (Rashid & Azizah, 2011), and Morocco (Berraho et al, 2012) and in Pakistan females had higher rates (Shafi & Shafi, 2017).…”
Section: Discussionmentioning
confidence: 99%